Attitudes and perceptions of teachers toward mental health literacy: A case of Odzi High School, Mutare District, Zimbabwe - Sibanda, Theresi; Sifelani, Innocent; Kwembeya, Maurice; Matsikure, Memory; Songo, Sifikile (Frontiers in Psychology, 2022)
In dealing with adolescent mental health teachers and school institutions have a critical role in minimizing challenges of mental health. However, success of such a measure is depended on teachers’ attitudes and perceptions on mental health literacy. Adolescent mental health disorders have become a major global concern with heightened increases and prevalence in secondary schools. In Zimbabwe a dearth of knowledge exists in understanding the perceptions and attitudes of teachers in maximizing student mental health and positive educational outcomes. The aim of the research was to understand attitudes and perceptions of teachers towards mental health literacy. Using a qualitative approach to understand attitudes and perceptions a case study was carried out at Odzi high school. A total of twelve teachers were purposively sampled for data generation on knowledge, attitudes, perceptions, and strategies that can be used to inform adolescent mental health. Data was collected using semi structured interview(s). Emergent themes of the study were; knowledge, stigma, training and development. Using thematic analysis, data showed that there was generalized knowledge on mental health, there were disparities in effective and efficient responses with gender sensitivity issues. Additionally, this knowledge was not put into practice because of attitudes and perceptions towards mental health. Recommendations from the study are development of mental health trainings for teachers, equipping teachers with skills in psychosocial support in schools’ mental health, enabling teachers to be able to link adolescents to appropriate care within the school and community-based settings. Teachers have the responsibility of promoting well-being, minimizing the adverse effects. Outcomes for positive mental health may be a result of teachers’ informed perceptions and positive attitudes on mental health literacy.